Supervision in the Digital Age: Leveraging Technology to Enhance Teacher Development - Nurtamami (Universitas Nurul Jadid, 2024)
This study focuses on the role of technology in enhancing the effectiveness of supervision by madrasah supervisors in Kraksaan District to improve teacher competence. Using a qualitative approach and case study method, data were collected through desk reviews, structured interviews, and observations involving madrasah supervisors, teachers, and principals. The study reveals that digital platforms can improve the efficiency of supervision by facilitating real-time feedback, enhancing collaboration, and accelerating the professional development of teachers. Despite these benefits, the implementation of technology in supervision faces significant challenges, including limited infrastructure, low digital literacy among supervisors, and inadequate policy support. The findings suggest that addressing these barriers through structured digital literacy training, improved access to technology infrastructure, and supportive policies could amplify the benefits of technology-based supervision. This study also highlights the potential of technology to transform traditional supervision methods, offering a more flexible and effective approach to professional development in madrasahs. The implications of this research emphasize the need for sustainable strategies to integrate technology into educational supervision practices, ensuring its long-term impact on teacher competence and educational quality. These results provide valuable insights for policymakers, educators, and researchers aiming to develop and implement technology-based supervision models in diverse educational contexts.